Financial institutions and economic growth of India - Goyal, O.P. (New Delhi, 1979)
ATTAINMENT of a continuous higher rate of growth in the economy has now become the prime goal of development in almost all the countries of the world irrespective of their degree of development as also of differences that exist in their political and social structure. Being an extremely intricate phenomenon, economic growth is influenced by more than one category of interrelated factors which may broadly relate to the physical, technological, psychological, financial, structural and institutional aspects of an economy. Moreover, the process of economic growth is so complex that it is generally not possible to assess separately the contribution of each factor which influences it.
Keywords: Financial institutions India